QbD-Guided Comparative Evaluation of RP-HPLC and UV Methods for Montelukast Sodium Quantification (Dhaka University Journal of Pharmaceutical Sciences, 2025)
This study focuses on establishing a fast and novel RP-HPLC method along with its comparable UV spectroscopic approach for the routine evaluation of montelukast sodium. Using Design Expert software, a 3² full-factorial design was deployed to optimize the RP-HPLC method. Retention time, tailing factor, and theoretical plate count were considered as the dependent response parameters in this design, and the mobile phase composition and its flow rate were chosen as the independent variables. A mobile phase composed of methanol and water (40:60, %v/v) was eluted through a C18 column (250 × 4.6 mm, 5 μm) at a flow rate of 1.0 mL/min for the chromatographic separation. The wavelength used for detection was 344.4 nm to ensure optimal sensitivity for the analyte. The RP-HPLC method development yielded statistically significant models (p